2013
DOI: 10.1111/ppa.12150
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a set of standard area diagrams to aid in estimation of spot blotch severity on wheat leaves

Abstract: This study aimed to develop and validate a standard area diagram (SAD) set to quantify the severity of spot blotch, caused by Bipolaris sorokiniana, on wheat leaves. The proposed SAD set includes images of leaves with 11 distinct disease severities (0Á1, 1, 5, 10, 20, 30, 40, 50, 60, 70 and 83%). The SAD set was validated by 12 raters without experience in evaluating plant disease. Lin's concordance correlation analysis of estimated versus actual disease severity (based on image analysis) showed that precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Overall, the use of SADs helps standardize raters, improving inter-rater reliability (itself a result of the accuracy of estimates of severity on individual specimens). Agreement (ρ c ) on the 0 to 100% range with actual values from image analysis frequently > 0.90 when using SADs (Spolti et al 2011;Duarte et al 2013;Domiciano et al 2014;González-Domínguez et al 2014). This can be considered excellent agreement in measurement science (Altman 1991), although others are more conservative (McBride 2005).…”
Section: Methods To Improve Accuracy Of Estimatesmentioning
confidence: 88%
“…Overall, the use of SADs helps standardize raters, improving inter-rater reliability (itself a result of the accuracy of estimates of severity on individual specimens). Agreement (ρ c ) on the 0 to 100% range with actual values from image analysis frequently > 0.90 when using SADs (Spolti et al 2011;Duarte et al 2013;Domiciano et al 2014;González-Domínguez et al 2014). This can be considered excellent agreement in measurement science (Altman 1991), although others are more conservative (McBride 2005).…”
Section: Methods To Improve Accuracy Of Estimatesmentioning
confidence: 88%
“…Consequently, estimates made without SADs had small bias, and were relatively precise, accurate and reliable, with only a few exceptions. Other studies have demonstrated that SADs are effective aids, particularly for inexperienced raters (Nutter et al ., ; Nutter & Esker, ; Godoy et al ., ; Domiciano et al ., ; Yadav et al ., ; Schwanck & Del Ponte, ). Significant improvement in bias, accuracy, precision and inter‐rater reliability showed some trends but were not entirely consistent.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were found in previous studies conducted by several researchers (ALVES et al, 2015;CAPUCHO et al, 2011;CUSTÓDIO ET AL., 2011;DOMICIANO et al, 2013;DUARTE et al, 2013;JULIATTI et al, 2013;LENZ et al, 2010;LIMA et al, 2013;NUNES;ALVES, 2012;REIS, CASA;BRESOLIN., 2013;SOUSA et al, 2014;TERAMOTO et al, 2011;TROJAN;PRIA, 2018), showing an increase in precision after using a diagrammatic scale, demonstrating the importance of this tool in quantifying disease severity.…”
Section: Evaluatormentioning
confidence: 99%